(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Global warming is the resulting climate change is among the foremost serious environmental problems facing by the world community. It’s the fact which happening with the issues of climate variability and alter and it deals with descriptions, causes, implications, interactions, impact and responses among other causes. From many decades, heating is occurring but it’s not clearly visible. A number of the recent impacts round the world include increases in extreme weather events, rising water level, disappearing glaciers and polar ice, damaged coral, changes in wild life distributions and health, and increased activity of abundance of disease vectors. Dangerous heat waves are increasing in severe frequency and water level rise is accelerating. Extreme storms are rising in some areas and severe droughts are occurring in others. Collectively these effects pose a threat to the whole planet including we, our family and our community. The current study aims to search out out the worldwide research output of the scientists in the field of world warming. Because it is the subject of the hour the necessity for the current study increases plenty. The study helps the future scientists to try to make more effort to find out the disciplines and the range of the sector in an analogous manner. Present research study also attempted to quantify the research output of global warming to guage its impact on climate specially Indian Climate.